New subgenus and new species of marine benthic ostracods of genus Doloria (Ostracoda; Myodocopina) from the Southern Ocean - Chavtur, Vladimir G.; Brandão, Simone N.; Bashmanov, Alexander G. (Zootaxa, 2012)
The project ANDEEP was designed to fill gaps in the knowledge of the biodiversity of the Southern Ocean deep sea. Threeoceanographic cruises (ANDEEP I, II and III) were undertaken in 2002 and 2005 in the Atlantic Sector of the SouthernOcean. Hundreds of samples were collected from 40 stations with water depths ranging from 748 to 6,348 m. Investiga-tions were carried out on a broad range of taxa, including bacteria, meio-, macroand megafauna. Approximately 5000ostracods were collected, which included 29 specimens of Doloria (Dolorietta) subgen. nov.The subdivision of the genus Doloria Skogsberg, 1920 into two subgenera, Doloria (Doloria) and the novel subgenusDoloria (Dolorietta), is based on differences in the structures of the fifth limb, the armature of the sensory bristle on the5th segment of the antennula, and the number of bristles on the 4th endite of the sixth limb. Four new species in the newsubgenus were identified from the ANDEEP samples. The new subgenus and the four novel species are described andillustrated. Two of these new species are named Doloria (Dolorietta) antarctica sp. nov. and Doloria (Dolorietta) sextafiliformis sp. nov., but the other two species are left in open nomenclature (i.e. Doloria (Dolorietta) sp. nov. 1 and Doloria(Dolorietta) sp. nov. 2) because only juveniles were found in our material. Keys to the subgenera and species of Doloria are provided.